Sb-Doped high-voltage LiCoO2 enabled improved structural stability and rate capability for high-performance Li-ion batteries. Issue 35 (12th April 2022) - Chen, Cong; Li, Tianyu; Yang, Xiaofei; Qu, Chao; Luo, Yang; Wang, Yuxiao; Zhang, Huamin; Zhang, Hongzhang; Li, Xianfeng
Abstract : Sb-Doped high-voltage LiCoO2 was developed with unique properties. Abstract : Sb-Doped high-voltage LiCoO2 was developed with unique properties. In situ X-ray diffraction and density functional theory reveal that the introduction of Sb helps to shorten the Li + diffusion distance, increase the lattice spacing and keep the structural stability during deep lithiation, thus resulting in improved rate capability and cycling performance.